The Production Function and the Theory of Capital - Solow, Robert M. (Review of Economic Studies, 1955)
Journal Article The Production function and the Theory of Capital Get access Robert M. Solow Robert M. Solow Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 101–108, https://doi.org/10.2307/2296293 Published: 01 January 1955